Spectrum of movement disorders: Experience of a one and half year of existence of the first specialized center in Senegal. (May 2022) - Fall, Maouly; Dardare, Ibrahim M.; Diop, Alassane M.; Pelagie, Michel A.; Kahwagi, Jamil; Dechacus, Ghislain C.; Gaye, Ndiaga M.; Rizig, Mie; Diagne, Ngor S.; Ndiaye, Moustapha; Diop, Amadou G.
Abstract: Background: Movement disorders have different prevalence in different regions and they are little studied in Africa. Objectives: Evaluate the prevalence and determine the spectrum of movement disorders in the first specialized center in Senegal. Methods: It was a prospective study over on 18 months in adult outpatient clinic. Demographic, clinical, paraclinical data, including genetic test in collaboration with the Queen Square Institute of Neurology at UCL were collected. Results: One hundred and thirty four patients were followed up, representing a prevalence of 4.7%. Men represented 56% for a sex ratio of 1.3. The mean age of population was 47.7 ± 18 years with limits ranging from 16 to 81 years. Eighty-one patients (60.4%) had hyperkinetic and 53 patients (39.6%) had hypokinetic movements. Twenty-nine patients (21.6%) had tremors and 18 (13.4%) had dystonic movements. Ataxia and choreic movements were respectively in 11 (8.2%) and 10 patients (7.5%). Twenty-four patients (17.9%) were from a first-degree consanguineous. A genetic test on saliva samples was done in 16 patients (11.9%) and confirmed Huntington's disease in 8 patients of 6 families. Parkinson disease was the most frequent etiology (32.8%) followed by essential tremor (12.7%) and psychogenic tremor in 7.5%. Stroke accounted for 6% of the causes of MD (tremor, ballism, dystonia, ataxia and parkinsonism) and no etiology was found in 9%. Conclusion: The spectrum of movement disorders is very heterogeneous with a non-negligible frequency and diverse etiologies in neurological practice in Senegal. Highlights: Movement disorders are not uncommon in developing countries, but they are under-studied, especially in sub-Saharan Africa. With the aging of the world population, the incidence and prevalence of neurodegenerative diseases including movement disorders are likely to increase in sub-Saharan Africa. Their prevalence in Africa varies according to the series and Parkinson's disease remains the most frequent etiology. Their diagnosis remains limited by the difficulty of having genetic explorations in developping countries.